MENGENAL TIGA PILAR KUALITAS SOAL: DAYA BEDA, TINGKAT KESUKARAN, DAN PENGECOH - Wafda Sabilla; Ma'mun Hanif; Indah Ayu Febriana; Slamet Gunawan; Kharis Barik Lana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Item quality is an important factor in determining the validity and reliability of educational evaluation instruments. This study aims to examine three main pillars in item quality analysis, namely discriminating power, difficulty level, and distractor effectiveness, in the context of improving the quality of multiple-choice evaluation instruments in learning activities. This study uses a literature study method by collecting and synthesizing various scientific references related to the topic studied including books, national journals, and articles obtained through Google Scholar. The findings of the study revealed that discriminating power has a primary function as a tool to differentiate between students with high abilities and students with low abilities, with an ideal index value that should reach ≥ 0.40. The difficulty level describes the degree of ease or difficulty of a question item, with an ideal index in the medium range of 0.31–0.70. Meanwhile, distractor effectiveness refers to the ability of incorrect answer alternatives to influence students who have not yet mastered the material to choose it. A distractor is considered to function well and is declared effective if it is chosen by at least 5% of the total participants who take the test. These three components are interrelated and complementary in determining the overall quality of a test item. This research's contribution lies in providing a comprehensive theoretical framework for educators to analyze and improve the quality of evaluation instruments, ensuring that the tests used in the assessment process accurately, validly, and reliably measure student learning outcomes.